2018
DOI: 10.3892/mco.2018.1766
|View full text |Cite
|
Sign up to set email alerts
|

A multi‑center retrospective analysis of the effect of DPP4 inhibitors on progression‑free survival in advanced airway and colorectal cancers

Abstract: Cluster of differentiation 26 (CD26), also known as dipeptidyl peptidase IV (DPP4), is a cell surface protein with exopeptidase activity and is expressed by most cell types. CD26/DPP4 is a multifunctional molecule with diverse biological effects, including regulatory effects on tumor growth, invasion and metastasis, and is a potential novel therapeutic target for selected cancers. In this study, we retrospectively analyzed diabetic patients with concurrent advanced airway or colorectal cancer to examine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 22 publications
0
33
1
4
Order By: Relevance
“…Our study included two groups of cancers, CRC and lung cancers, which have a different clinical course. We included the same group of cancers as we included in our initial retrospective study . With a larger sample size, our present study showed statistically significant HR in the combined cohort of CRC and lung cancer patients.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our study included two groups of cancers, CRC and lung cancers, which have a different clinical course. We included the same group of cancers as we included in our initial retrospective study . With a larger sample size, our present study showed statistically significant HR in the combined cohort of CRC and lung cancer patients.…”
Section: Discussionmentioning
confidence: 88%
“…Due to these in‐vivo studies showing that DPP4/CD26 inhibition can either deter or facilitate tumor progression, we previously conducted a multi‐institutional retrospective study involving patients with advanced airway and colorectal cancers (CRCs) who were being treated for diabetes with DPP4 inhibitors. Our study, which to our knowledge was the first study evaluating the role of DPP4 inhibition on cancers in human subjects, found statistically significant benefit in progression‐free survival and a positive trend in overall survival (OS); however, this benefit in OS did not reach the level of statistical significance, likely due to the relatively small number of subjects included in the study . As a follow‐up and to further clarify the role of DPP4 inhibitors in human malignancies, we conducted a national database study in CRC and lung cancer.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, DPP-4 can act either as a tumor activator or suppressor depending on paracrine signals, the microenvironment, and molecular interactions [42,43]. The pharmacological inhibition of DPP-4 in lung cancer patients showed improved overall survival, which was attributed to the effect of DPP-4 inhibition on tumor immunoregulation [44,45]. Information on the role of DPP-4/CD26 in tumor biology can be inferred from either transgenic animals that lack DPP-4 or its pharmacological inhibition.…”
Section: Dpp-4 and Lung Cancermentioning
confidence: 99%
“…Metastasis and tumor invasion are dependent upon matrix degradation, which allows cell mobility and tissue penetration. DPP-4/CD26 has been shown to have a pivotal role in both tumor cell metastasis and invasion [45,50]. There are a variety of suggested mechanisms for DPP-4 to impinge on cancer metastasis.…”
Section: Dpp-4 and Lung Cancermentioning
confidence: 99%